Characteristics of Patients with Urinary Tract Infection - Halmina Ilyas; Suradi Efendi; Asri Yuliawaty (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Urinary tract infection is caused by pathogenic microorganisms ascending from the urethra to the bladder and increasing in number, then evoking infection of the ureters and kidneys. The incidence of urinary tract infection at Pelamonia Hospital in 2018 was 1094 cases, and from January to August in 2019, the number of cases was 944 cases, while for the last three months data were 321 cases. The purpose of this study was to describe the characteristics of patients with urinary tract infection. This study is a descriptive study using the Accidental Sampling design. The sample in the study was 38 people who were diagnosed with urinary tract infection at Pelamonia Hospital. The data were collected using a questionnaire. The results of this study showed that from 38 respondents with urinary tract infection (UTI), the average age was mostly between 56-65 years as many as 14 (36.8%) respondents, most of them were female as many as 20 (52.6%) respondents, most are high school graduates as many as 25 (65.8%) respondents, most only have sufficient knowledge as many as 35 (92.1%) respondents, and mostly occurred in the accustomed to holding urination group as many as 34 (89.5%) respondents. The conclusions of this study indicate that the characteristics of patients with Urinary Tract Infection (UTI) such as age, gender, education level, knowledge, and accustomed to hold urination play a role in the incidence of urinary tract infection.